Prognostic significance of pancreatic fistula and postoperative complications after pancreaticoduodenectomy in patients with pancreatic ductal adenocarcinoma. Issue 1 (February 2020) - Neeman, Uri; Lahat, Guy; Goykhman, Yaacov; Geva, Ravit; Peles-Avraham, Sharon; Nachmany, Ido; Nakache, Richard; Klausner, Joseph M.; Lubezky, Nir
Abstract: Background: The influence of postoperative complications, specifically, pancreatic fistula (PF), on long-term oncologic outcome in patients with pancreatic ductal adenocarcinoma (PDAC) is unclear. Methods: Prospectively collected data of patients who underwent pancreaticoduodenectomy (PD) for PDAC between 2008 and 2016 were retrospectively reviewed and analyzed. Deaths within 90 days were excluded. Median follow-up time was 22 months for the entire cohort (range 2–102 months). PF was graded as biochemical leak, grade B, or grade C according to the criteria of the International Study Group on Pancreatic Fistula. Postoperative complications were graded according to the Clavien-Dindo classification (CDC). Data on clinical and pathological characteristics as well as on recurrence and survival were collected. Results: Twenty-nine of the 148 identified patients (19%) developed PF, of whom 17 (11.4%) had a PF grade B or C. 29 patients developed a postoperative complication CDC grade 3 or 4. The respective 3-year disease-free survival was 15.5% and 19.2% ( P = 0.725), and the 5-year overall survival was 20% and 16% ( P = 0.914) in patients with and without PF. On multivariate analysis, the use of adjuvant chemotherapy, lymph node involvement, surgical margin involvement, and tumor grade were associated with patient survival. PF and postoperative complications CDC grade 3 or 4 were not associated with decreased long-term survival, disease-free survival or local recurrence rate. Conclusions: While acknowledging the limited sample size, no association was seen between PF or postoperative complications and overall or disease-free survival in patients undergoing PD for PDAC.